Lid material and method for manufacturing the same
Patent Information
- Application Number
- JP2023127951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0017】 本発明によれば、湿度の変化に起因するカールの発生及びヒートシール時のブリスターの発生を低減又は抑制することができる蓋材及びその製造方法を提供することができる。
Smart Images

Figure 2025023633000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a covering material and a method for producing the same. [Background technology]
[0002] In recent years, various researches have been conducted on paper-based covering materials.
[0003] For example, Patent Document 1 discloses a covering material that is characterized by being a laminate consisting of at least a biaxially oriented plastic film having a water-retaining layer on one side of paper and a vapor-deposited film of an inorganic oxide on the other side, an adhesion adjustment layer, and a hot melt layer.
[0004] Patent Document 2 discloses a heat-sealable lid material comprising a laminated sheet including a paper layer supplied with a water retention agent and the innermost layer being a hot melt layer, in which a light-shielding ink layer is laminated on at least the inner side of the paper layer, and the lid material has a light transmittance of 15% or less in the wavelength range of 200 to 800 nm.
[0005] Patent Document 3 discloses a paper cup lid material characterized by being formed by laminating a paper layer, an adhesive layer, a biaxially oriented plastic film layer, and a hot melt layer in this order.
[0006] Patent Document 4 discloses a lid material that is heat-sealed to a cup-shaped container having a resin layer formed on at least the surface, the lid material being made of a composite sheet having a paper intermediate layer and a resin layer or an aluminum foil layer on both the front and back sides of the paper, the lid material being characterized in that the air permeability of the paper is 10 seconds or less as measured by the JIS P8117 Gurley tester method. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2000-118546 A [Patent Document 2] JP 2000-006295 A [Patent Document 3] Japanese Patent Application Publication No. 09-066586 [Patent Document 4] JP 2004-196381 A Summary of the Invention [Problem to be solved by the invention]
[0008] It has been known that general-purpose paper lid materials tend to curl, and some solutions have been proposed to address this problem, such as providing a water-retaining layer on the paper base material or using a paper layer to which a water-retaining agent has been added.
[0009] However, when a humectant or water-retaining agent is applied to a paper substrate, curling can be suppressed during the manufacture of the lid material, but there is a problem that curling occurs when the manufactured lid material is placed in an environment with variable humidity. More specifically, for example, a lid material manufactured by applying a mixed liquid of water and methanol to the back surface of a paper substrate can suppress the occurrence of convex curling under high humidity conditions, but has a problem that concave curling occurs under low humidity conditions.
[0010] In response to this, for example, a lid material has been proposed in which a resin layer or an aluminum foil layer is provided on both sides of a paper base material. Since this type of paper base material allows relatively little moisture to enter or leave, it is possible to suppress curling caused by changes in humidity.
[0011] However, in a lid material having a resin layer or an aluminum foil layer on both sides of a paper base material, the heat applied when heat-sealing the lid material to a container or the like may cause the moisture contained in the paper base material to evaporate, generating high-temperature water vapor within the paper base material of the lid material. In particular, in the case of a lid material having a resin layer or an aluminum foil layer on both sides of the paper base material, the generated water vapor has nowhere to escape except through the end face of the paper base material of the lid material, which causes a problem that a partial peeling phenomenon (this phenomenon is also called "blistering" or "bubbling") occurs within the lid material, for example, at the adhesive surface between the paper base material and the resin layer or aluminum foil layer.
[0012] On the other hand, if a paper base material with a small air permeability value (i.e., a paper base material that is easily permeable) is used, it is possible to suppress the occurrence of the above-mentioned blisters, but since the inflow and outflow of moisture becomes relatively intense, it becomes impossible to suppress the occurrence of curling. In addition, when a paper base material with a small air permeability value is used, there is a possibility that the printability will be deteriorated.
[0013] As described above, it is difficult for a covering material to simultaneously prevent curling due to changes in humidity and prevent the occurrence of blisters during heat sealing.
[0014] The present invention seeks to improve the above-mentioned circumstances, and its object is to provide a covering material and a manufacturing method thereof that can reduce or suppress the occurrence of curling due to changes in humidity and the occurrence of blisters during heat sealing. [Means for solving the problem]
[0015] The present invention which achieves the above object is as follows.
[0016] <Aspect 1> A lid material having a print layer, a paper layer, and a sealant layer, wherein the lid material is dried in a vacuum oven at 60°C for 4 hours, and when the lid material is seasoned for 60 minutes in an environment of 23°C and 50% RH (relative humidity) based on the mass after drying, the moisture absorption amount is 3.2 g / m 2 is as follows: The paper layer is coated with a resin coating agent from the printing layer side on the paper base layer, and The laminate of the printed layer and the paper layer has an air permeability of 150,000 seconds or less when measured from the paper base layer side to the printed layer side using the Oken type testing machine method of JIS P8117:2019. Lid material. <Aspect 2> The coating amount of the resin coating agent is 0.5 to 3.0 g / m 2 The covering material according to embodiment 1, <Aspect 3> 3. The covering material according to claim 1 or 2, wherein the resin coating agent comprises a resin selected from the group consisting of polyvinylidene chloride, polyester, polyvinyl alcohol, and combinations of two or more thereof. <Aspect 4> Further comprising a barrier layer; The covering material according to any one of aspects 1 to 3, comprising the print layer, the paper layer, the barrier layer, and the sealant layer in this order. <Aspect 5> 5. The covering material according to embodiment 4, wherein the barrier layer is selected from the group consisting of a metal foil layer, an inorganic vapor deposition layer, an organic coating layer, and a combination of two or more of these. <Aspect 6> The covering material according to any one of aspects 1 to 5, wherein the printed layer has an ink layer and an overprint varnish layer on the ink layer. Aspect 7 A method for producing the covering material according to any one of aspects 1 to 6, comprising applying the resin coating agent to a surface of the paper base layer that is to be laminated with the printed layer, to obtain the paper layer. <Aspect 8> 8. The method of claim 7, wherein the resin coating comprises a resin selected from the group consisting of polyvinylidene chloride, polyester, polyvinyl alcohol, and combinations of two or more thereof. Effect of the Invention
[0017] According to the present invention, it is possible to provide a covering material and a manufacturing method thereof that can reduce or suppress the occurrence of curling due to changes in humidity and the occurrence of blisters during heat sealing. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the layer structure of the covering material of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of the layer structure of the printing layer according to the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing one embodiment of the layer structure of the covering material of the present invention when it further comprises a barrier layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. Note that the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the present invention.
[0020] 《Lid material》 The lid material of the present invention is A lid material having a printing layer, a paper layer, and a sealant layer, The lid material was dried in a vacuum oven at 60°C for 4 hours, and the mass after drying was used as the standard. When the lid material was seasoned for 60 minutes in an environment of 23°C and 50% RH (relative humidity), the moisture absorption amount was 3.2 g / m 2 is as follows: The paper layer is coated with a resin coating agent from the printing layer side on the paper base layer, and The laminate of the printed layer and the paper layer has an air permeability of 150,000 seconds or less when measured from the paper base layer side to the printed layer side using the Oken testing machine method of JIS P8117:2019. Lid material It is.
[0021] The lid material of the present invention can reduce or suppress the occurrence of curling due to changes in humidity and the occurrence of blisters during heat sealing. Without being limited by theory, it is assumed that this is mainly due to the effect of limiting the moisture absorption amount of the lid material of the present invention to a certain value or less, and limiting the air permeability value of the laminate of the print layer and the paper layer contained in the lid material of the present invention to a certain value range or less. More specifically, the lid material of the present invention is dried in a vacuum oven at 60°C for 4 hours, and when the mass after drying is used as the standard, it is seasoned in an environment of 23°C and 50% RH (relative humidity), and the moisture absorption amount in 60 minutes is 3.2 g / m 2 By setting the temperature below 150,000 seconds, the inflow and outflow of moisture can be relatively suppressed. That is, the lid material of the present invention can reduce or suppress the occurrence of curling even when placed in an environment with humidity changes. In addition, in the lid material of the present invention, when the air permeability value of the laminate of the printed layer and the paper layer is measured from the paper base layer side toward the printed layer side by the Oken type testing machine method of JIS P8117:2019, by setting the air permeability value to 150,000 seconds or less, the laminate of the printed layer and the paper layer becomes more air permeable, that is, the lid material of the present invention can reduce or suppress the occurrence of blisters even when heated when heat-sealed to a container or the like.
[0022] <Characteristics of the lid material> (Moisture absorption amount) The moisture absorption amount of the lid material of the present invention can be determined by the following method. That is, for example, the lid material is placed in a roughly circular shape with a diameter of 101 mm (area: 0.00824 m 2 ), then dried in a vacuum oven at 60°C for 4 hours, and the mass after drying is taken as the reference (0 (zero)). Next, the dried lid material is seasoned in an environment of 23°C and 50% RH (relative humidity), while the change in mass over time is measured. Then, the amount of moisture absorbed after a specific time (for example, after 60 minutes, 40 minutes, or 20 minutes) can be calculated based on the following formula. Moisture absorption (g / m 2 ) = mass after moisture absorption (g / m 2 )-Mass after drying in a vacuum oven (g / m 2 )
[0023] The amount of moisture absorption of the covering material of the present invention after 60 minutes at 23°C and 50% RH (relative humidity) is 3.2 g / m 2 More specifically, the moisture absorption amount under these conditions is 3.2 g / m 2 Below, 3.1g / m 2 Below 3.0g / m 2 Below, 2.9g / m 2 Below 2.8g / m 2 Below 2.7g / m 2 Below, 2.6g / m 2 Below 2.5g / m 2 Below 2.4g / m 2 Below, 2.3g / m 2 Below, 2.2g / m 2 Below, 2.1g / m 2 Below 2.0g / m 2 Below, 1.9g / m 2 Below 1.8g / m 2 Below 1.7g / m 2 Below 1.6g / m 2 Below 1.5g / m 2 Below 1.4g / m 2 Below 1.3g / m 2 Below 1.2g / m 2 Below, 1.1g / m 2 Less than or equal to 1.0 g / m 2 The lower limit of the moisture absorption amount under these conditions is not particularly limited, and may be, for example, 0.0 g / m 2 More than 0.0g / m 2 Ultra, 0.1g / m 2 More than 0.2g / m 2 More than 0.3g / m 2 More than 0.4g / m 2 More than 0.5g / m 2 More than 0.6g / m 2 More than 0.7g / m 2 More than 0.8g / m 2 More than 0.9g / m 2 or more, or 1.0 g / m 2 It may be more than that.
[0024] The moisture absorption amount of the covering material of the present invention after 40 minutes at 23° C. and 50% RH (relative humidity) as determined by the above method is not particularly limited, and may be, for example, 3.0 g / m 2 Below, 2.9g / m 2 Below 2.8g / m 2 Below 2.7g / m 2 Below, 2.6g / m 2 Below 2.5g / m 2 Below 2.4g / m 2 Below, 2.3g / m 2 Below, 2.2g / m 2 Below, 2.1g / m 2 Below 2.0g / m 2 Below, 1.9g / m 2 Below 1.8g / m 2 Below 1.7g / m 2 Below 1.6g / m 2 Below 1.5g / m 2 Below 1.4g / m 2 Below 1.3g / m 2 Below 1.2g / m 2 Below, 1.1g / m 2 Less than or equal to 1.0 g / m 2 or less, and may be 0.0 g / m 2 More than 0.0g / m 2 Ultra, 0.1g / m 2 More than 0.2g / m 2 More than 0.3g / m 2 More than 0.4g / m 2 More than 0.5g / m 2 More than 0.6g / m 2 More than 0.7g / m 2 More than 0.8g / m 2 More than 0.9g / m 2 or more, or 1.0 g / m 2 It may be more than that.
[0025] Furthermore, the moisture absorption amount of the covering material of the present invention after 20 minutes at 23° C. and 50% RH (relative humidity) as determined by the above method is not particularly limited, and is, for example, 2.0 g / m 2 Below, 1.9g / m 2 Below 1.8g / m 2 Below 1.7g / m 2Below 1.6g / m 2 Below 1.5g / m 2 Below 1.4g / m 2 Below 1.3g / m 2 Below 1.2g / m 2 Below, 1.1g / m 2 Below 1.0g / m 2 Below, 0.9g / m 2 Below, 0.8g / m 2 Below, 0.7g / m 2 Below, 0.6g / m 2 or less than 0.5g / m 2 or less, and may be 0.0 g / m 2 More than 0.0g / m 2 Ultra, 0.1g / m 2 More than 0.2g / m 2 More than 0.3g / m 2 More than 0.4g / m 2 or more, or 0.5 g / m 2 It may be more than that.
[0026] In the present invention, the moisture absorption amount of the covering material can be appropriately adjusted by, for example, the type and coating amount of the resin coating agent applied to the paper base layer.
[0027] (Thickness) The thickness of the lid material of the present invention is not particularly limited, and may be, for example, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, or 150 μm or more, and may be 200 μm or less, 180 μm or less, 150 μm or less, 120 μm or less, or 100 μm or less.
[0028] <Layer structure of the lid material> The layer structure of the lid material of the present invention will be described below by way of example with reference to the drawings. For the sake of convenience, the same or corresponding parts in each drawing are given the same reference numerals, and duplicated explanations will be omitted. In addition, not all components of the embodiment are essential, and some components may be omitted. However, the embodiments shown in the following drawings are merely examples of the present invention, and do not limit the present invention.
[0029] FIG. 1 is a schematic cross-sectional view showing one embodiment of the layer structure of the covering material of the present invention.
[0030] 1, the lid material 100 of the present invention has a print layer 10, a paper layer 20, and a sealant layer 30. The paper layer 20 is made of a paper base layer 20b coated with a resin coating agent 20a from the print layer 10 side. Usually, the print layer 10 side of the lid material 100 is the front layer side and the sealant layer 30 side is the back layer side, and the lid material 100 can be heat sealed to a container or the like via the sealant layer 30.
[0031] (Printing layer) The covering material of the present invention has a printed layer. The printed layer can be used as a functional layer for blocking light or ultraviolet rays, in addition to being provided with a pattern, text information, or the like.
[0032] In the present invention, the thickness of the printing layer is not particularly limited and may be, for example, 0.1 μm or more, 0.5 μm or more, 1.0 μm or more, 2.0 μm or more, 3.0 μm or more, 4.0 μm or more, 5.0 μm or more, 6.0 μm or more, 7.0 μm or more, 8.0 μm or more, 9.0 μm or more, or 10 μm or more, and may be 10 μm or less, 8.0 μm or less, 5.0 μm or less, 3.0 μm or less, or 1.0 μm or less.
[0033] In the present invention, the printing layer may, for example, have only an ink layer, or may have an ink layer and an overprint varnish layer on the ink layer.
[0034] FIG. 2 is a schematic cross-sectional view showing one embodiment of the layer structure of the printing layer according to the present invention.
[0035] The printed layer 10 shown in Fig. 2 has, from the back layer side to the front layer side, an ink layer 10a and an overprint varnish layer 10b on the ink layer 10a. Although not shown in Fig. 2, in this case, the ink layer 10a is laminated on the paper layer side.
[0036] In the present invention, the ink layer of the printed layer is not particularly limited, and may contain, for example, an ink selected from the group consisting of a water-based ink, an oil-based ink, a curable ink, and a combination of two or more of these.
[0037] In the present invention, by providing an overprint varnish layer (also simply referred to as "OP varnish") on the ink layer of the printed layer, peeling of the printed layer can be reduced, and also, during the manufacturing process, for example, when the lid material is rolled up into a roll, show-through of the ink layer can be prevented.
[0038] In the present invention, the printing method is not particularly limited and may be, for example, gravure printing, flexographic printing, etc. In addition, when an overprint varnish layer is provided, it may be performed, for example, by printing a commercially available OP coating agent on the ink layer.
[0039] (paper layer) The covering material of the present invention has a paper layer. In addition, in the present invention, the paper layer can be obtained by applying a resin coating agent to the paper base layer from the side to be laminated with the printed layer. That is, the paper layer is coated with a resin coating agent from the printed layer side on the paper base layer.
[0040] In the present invention, the coating amount of the resin coating agent in the paper layer is not particularly limited, and may be, for example, 0.5 g / m 2 More than 0.6g / m 2 More than 0.7g / m 2 More than 0.8g / m 2 More than 0.9g / m 2 More than 1.0g / m 2 More than 1.1g / m 2 More than 1.2g / m 2 More than 1.3g / m 2 More than 1.4g / m 2 More than 1.5g / m 2 More than 1.6g / m 2 More than 1.7g / m 2 More than 1.8g / m 2 More than 1.9g / m 2 or more, or 2.0 g / m 2or more, and 3.0 g / m 2 Below, 2.9g / m 2 Below 2.8g / m 2 Below 2.7g / m 2 Below, 2.6g / m 2 Below 2.5g / m 2 Below 2.4g / m 2 Below, 2.3g / m 2 Below, 2.2g / m 2 Below, 2.1g / m 2 Below 2.0g / m 2 Below, 1.9g / m 2 Below 1.8g / m 2 Below 1.7g / m 2 Below 1.6g / m 2 Below 1.5g / m 2 Below 1.4g / m 2 Below 1.3g / m 2 Below 1.2g / m 2 Below, 1.1g / m 2 Less than or equal to 1.0 g / m 2 It may be the following:
[0041] In the present invention, the resin coating agent is not particularly limited, and may include, for example, a resin selected from the group consisting of polyvinylidene chloride (PVDC), polyester, polyvinyl alcohol (PVOH), and a combination of two or more of them. The resin coating agent may be water-based or solvent-based. These resin coating agents may be commercially available.
[0042] In the present invention, the laminate of the above-mentioned printed layer and paper layer has an air permeability of 150,000 seconds or less when measured from the paper base layer side toward the printed layer side by the Oken type testing machine method of JIS P8117: 2019. More specifically, this air permeability value may be, for example, 150,000 seconds or less, 100,000 seconds or less, 90,000 seconds or less, 80,000 seconds or less, 70,000 seconds or less, 60,000 seconds or less, 50,000 seconds or less, 40,000 seconds or less, 30,000 seconds or less, or 20,000 seconds or less. The lower limit of the air permeability is not particularly limited, and may be, for example, 500 seconds or more, 1,000 seconds or more, 2,000 seconds or more, 3,000 seconds or more, 4,000 seconds or more, 5,000 seconds or more, 6,000 seconds or more, 7,000 seconds or more, 8,000 seconds or more, 9,000 seconds or more, 10,000 seconds or more, 20,000 seconds or more, 30,000 seconds or more, or 40,000 seconds or more. The air permeability value of the laminate of the printed layer and the paper layer is a value obtained by measuring from the back layer side of the paper layer toward the front layer side (printed layer side).
[0043] (Paper base layer) In the present invention, the paper base layer is not particularly limited as long as it satisfies the air permeability range of the laminate of the printed layer and the paper layer described above, and may be, for example, art paper, coated paper, pure white paper, or high-quality paper.
[0044] In the present invention, the basis weight of the paper base layer is not particularly limited, and may be, for example, 30 g / m 2 More than 40g / m 2 More than 50g / m 2 More than 60g / m 2 or more than 70g / m 2 or more, and 2 Below 150g / m 2 or less than 100g / m 2 It may be the following:
[0045] (Sealant layer) The lid material of the present invention has a sealant layer. The sealant layer is a layer for heat-sealing the lid material to a container to be sealed with the lid material.
[0046] The material of the sealant layer is not particularly limited and may be appropriately selected depending on the material of the container to be sealed. The material of the sealant layer may be, for example, a polyolefin resin or an ethylene vinyl acetate copolymer resin (EVA). These resins may be provided in the form of, for example, a stretched or unstretched film, a molten resin for extrusion lamination, a coating for hot melt, or the like.
[0047] The polyolefin resin is not particularly limited, and for example, a polyethylene resin or a polypropylene resin can be used.
[0048] In the present invention, the sealant layer may be an easy-peel sealant layer that has been imparted with easy peelability, such as an interfacial peeling type sealant layer made by mixing resins with different compositions, a cohesive peeling type sealant layer in which the sealant layer is made into multiple layers and the film peels off accompanied by cohesive failure when the sealant layer is opened, or an interlayer peeling type sealant layer in which the sealant layer is made into multiple layers, at least one layer is a layer that is fused to the container (sealing layer) and the other layer is a layer adjacent to the sealing layer (peeling layer) and peels off between the sealing layer and the peeling layer when the sealant layer is opened.
[0049] In the present invention, the thickness of the sealant layer is not particularly limited and may be, for example, 1.0 μm or more, 5.0 μm or more, or 10 μm or more, and may be 100 μm or less, 80 μm or less, 50 μm or less, or 20 μm or less.
[0050] (Other layers) The lid material of the present invention may further have other layers. The other layers are not particularly limited, and examples thereof include an intermediate layer, a barrier layer, and an adhesive layer. Below, other layers that may be included in the lid material of the present invention are described as examples, but the present invention is not limited to these layers.
[0051] [Barrier layer] The covering material of the present invention further comprises a barrier layer, and may have a print layer, a paper layer, a barrier layer, and a sealant layer in this order.
[0052] FIG. 3 is a schematic cross-sectional view showing one embodiment of the layer structure of the covering material of the present invention when it further comprises a barrier layer.
[0053] As shown in FIG. 3, the covering material 200 of the present invention has a print layer 10, a paper layer 20, a barrier layer 40, and a sealant layer 30 in this order.
[0054] In the present invention, the barrier layer is not particularly limited and may be selected from the group consisting of, for example, a metal foil layer, an inorganic vapor deposition layer, an organic coating layer, and a combination of two or more of these.
[0055] The metal foil layer is not particularly limited, and examples of metal foils that can be used include aluminum foil, copper foil, titanium foil, and alloy foils such as aluminum alloy foil and stainless steel foil.
[0056] The inorganic vapor deposition layer is not particularly limited, and for example, a silica vapor deposition film, an aluminum vapor deposition film, an alumina vapor deposition film, or a silica-alumina vapor deposition film can be used.
[0057] The organic coating layer is not particularly limited, and for example, a vinylidene chloride coating layer, a polyvinylidene fluoride coating layer, or a polyvinyl alcohol layer can be used.
[0058] In the present invention, when an inorganic vapor deposition film or an organic coating layer is used as the barrier layer, the thickness of the barrier layer may be, for example, from the viewpoint of ensuring strength and barrier properties, 40 nm or more, 100 nm or more, 200 nm or more, 300 nm or more, 500 nm or more, 700 nm or more, or 1.0 μm or more, and may be, for example, from the viewpoint of improving handleability as a lid material, 5.0 μm or less, 4.0 μm or less, 3.0 μm or less, or 2.0 μm or less.
[0059] In the present invention, when a metal foil layer is used as the barrier layer, the thickness of the barrier layer may be, for example, from the viewpoint of ensuring strength and barrier properties, 3.0 μm or more, 4.0 μm or more, 5.0 μm or more, or 6.0 μm or more, and may be, for example, from the viewpoint of improving handleability as a lid material, 50 μm or less, 30 μm or less, or 10 μm or less.
[0060] [Middle layer] The lid material of the present invention may further have an intermediate layer. The intermediate layer may be provided, for example, between the paper layer and the sealant layer, or, when a barrier layer is included, between the paper layer and the barrier layer, or between the barrier layer and the sealant layer. The intermediate layer may have the function of, for example, relieving stress applied to the lid material during heat sealing or reinforcing the mechanical strength of the lid material.
[0061] The material for the intermediate layer is not particularly limited, and examples of the material that can be used include polyethylene, polypropylene, copolymer resins of ethylene and / or propylene and / or α-olefins (1-butene, 1-hexene, 1-octene, etc.), ethylene-vinyl acetate copolymer resin (EVA), ethylene-methacrylic acid copolymer resin (EMAA), ethylene-methyl methacrylate copolymer resin (EMMA), ethylene-methyl acrylate copolymer resin (EMA), ethylene-ethyl acrylate copolymer resin (EEA), ethylene-butyl acrylate copolymer resin (EBA), ethylene-vinyl alcohol copolymer resin (EVOH), olefin-based resins such as olefin-based ionomer resins, polyester-based resins, polyamide-based resins, and various other thermoplastic resin components and mixtures thereof.
[0062] The thickness of the intermediate layer is not particularly limited, and may be, for example, 1.0 μm or more, 5.0 μm or more, 10 μm or more, or 15 μm or more, and may be 50 μm or less, 30 μm or less, or 15 μm or less.
[0063] [Adhesive layer] The covering material of the present invention may further have an adhesive layer. The adhesive layer may be provided, for example, between the paper layer and the sealant layer, or, in the case where a barrier layer is included, between the paper layer and the barrier layer, or between the barrier layer and the sealant layer.
[0064] The raw material for the adhesive layer is not particularly limited, and examples thereof include thermosetting resins such as urethane resin, acrylic resin, phenol resin, polyimide resin, and bismaleimide resin; ionizing radiation curable resins such as (meth)acrylate resin, epoxy resin, unsaturated polyester resin, urethane acrylate resin, and polyol acrylate resin; ultraviolet curable resins such as polyester acrylate, urethane acrylate, and epoxy acrylate; hot melt adhesives, water-soluble adhesives, emulsion adhesives, non-solvent laminating adhesives, and thermoplastic resins for extrusion lamination.
[0065] The thickness of the adhesive layer is not particularly limited and may be, for example, 1.0 μm or more, 5.0 μm or more, 10 μm or more, or 15 μm or more, and may be 50 μm or less, 30 μm or less, or 15 μm or less.
[0066] <<Production method of lid material>> The method for producing the covering material of the present invention includes applying a resin coating agent to the surface of a paper base layer that will be laminated with a printed layer to obtain a paper layer.
[0067] In the present invention, layers other than the paper layer that may be contained in the lid material may be formed using a coating method, a printing method, etc. Furthermore, the lamination method for each layer is not particularly limited, and may be an extrusion lamination method such as sand lamination or back lamination, a dry lamination method, a hot melt method, a non-solvent lamination method, or a combination of these methods.
[0068] <Uses of lid material> The application of the lid material of the present invention is not particularly limited, but the lid material of the present invention can be used, for example, to seal the opening of various container bodies. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0070] {Making the lid material 1} Example 1-1 A laminate having the following basic structure was manufactured as a lid material laminate. Note that the numbers in parentheses indicate "thickness (μm)" unless otherwise specified. [Basic configuration] OP varnish / ink layer / resin coating agent (coating amount: 1.5g / m 2 ) coated on the ink layer side of the paper base layer (basis weight: 79.1 g / m 2 ) / Adhesive layer (A) (15μm) / Barrier layer (6.5μm) / Adhesive layer (B) (18μm) / Sealant layer (15μm)
[0071] The materials used for each layer (raw material) in the above basic structure are shown in Table 1 below: [Table 1]
[0072] More specifically, a laminate for a lid material was produced according to the following steps (1) to (3): (1) A resin coating, an ink layer, and an OP varnish were printed in this order on a paper base layer. (2) The paper layer and the barrier layer were sandwich-laminated via an adhesive layer (A), and then an adhesive layer (B) was back-laminated. (3) A sealant layer was back-laminated onto the adhesive layer (B).
[0073] Example 1-2 Resin coating amount: 2.0g / m 2 A laminate for a lid material of Example 1-2 was produced in the same manner as in Example 1-1, except for changing the above.
[0074] Comparative Example 1-1 A laminate for a lid material of Comparative Example 1-1 was produced in the same manner as in Example 1-1, except that no resin coating agent was applied.
[0075] Comparative Example 1-2 A laminate for a lid material of Comparative Example 1-2 was produced in the same manner as in Comparative Example 1-1, except that a PET film was attached instead of the OP varnish.
[0076] Comparative Example 1-3 A laminate for a lid material of Comparative Example 1-3 was prepared in the same manner as in Example 1-1, except that no resin coating agent was applied and a mixed liquid of water and methanol was applied to the back surface of the paper base layer.
[0077] Measurement and Evaluation <Evaluation of Curl Occurrence> The laminates for lid materials of each of the examples and comparative examples prepared above were cut out with a single-sided die and processed into a lid shape (a round shape with a diameter of 101 mm).Then, the obtained samples of each laminate were seasoned for one day under an environment of 23°C and 50% RH (relative humidity).Next, after seasoning for 60 minutes under an environment of 21°C and 12% RH (relative humidity) (assuming winter) and 25°C and 70% RH (relative humidity) (assuming summer), curling was visually confirmed.
[0078] Regarding the occurrence of curling, samples in which curling was improved compared to the sample of Comparative Example 1-1 were evaluated as "OK", and samples in which curling was worsened were evaluated as "NG". The results are shown in Table 2. The curl of the sample of Comparative Example 1-1 was approximately cylindrical.
[0079] <Measurement of moisture absorption amount> Each sample was processed into a lid shape (approximately round shape with a diameter of 101 mm and an area of 0.00824 m 2) was dried in a vacuum oven (60°C, 4 hours). Thereafter, the change in mass over time was measured while seasoning in an environment of 23°C and 50% RH (relative humidity). The mass immediately after drying in the vacuum oven was taken as the reference (0 (zero)). Using the following formula, the mass after absorbing moisture for 20 minutes, 40 minutes, and 60 minutes was calculated as the amount of moisture absorbed. The results are shown in Table 2. Moisture absorption (g / m 2 ) = mass after moisture absorption (g / m 2 )-Mass after drying in a vacuum oven (g / m 2 )
[0080] <Evaluation of blister occurrence> Each sample processed into a lid shape was seasoned for one day in an environment of 20°C and 50% RH (relative humidity). The seasoned sample was then heat-sealed to a container (temperature: 150-160°C, pressure: 180 kgf, time: 1.3 seconds). The presence or absence of blisters was visually confirmed.
[0081] Regarding the occurrence of blisters, cases where there were no blisters or wrinkles were rated as "A", cases where wrinkles were generated were rated as "B", and cases where blisters were generated were rated as "C". The evaluation results are shown in Table 2.
[0082] <Air permeability measurement> The air permeability was measured for a laminate obtained by printing a resin coating agent, an ink layer, and an OP varnish agent in this order on a paper base layer. More specifically, the air permeability was measured from the back layer side of the paper layer (i.e., the paper base layer side) to the front layer side of the paper layer (i.e., the printed layer side). The measurement was performed using an Oken type testing machine method. The measurement results are shown in Table 2.
[0083] [Table 2]
[0084] As is clear from Table 2, the covering materials of Examples 1-1 and 1-2 had improved curling compared to Comparative Example 1-1, and also suppressed the occurrence of blisters in heat sealing up to 160°C.
[0085] Moreover, from the results of measuring the amount of moisture absorption over time, it was found that the covering materials of Examples 1-1 and 1-2 had a significantly slower moisture absorption rate than the respective comparative examples.
[0086] In addition, the lid material of Comparative Example 1-3 did not have a slower moisture absorption rate, but convex curl was suppressed under high humidity (25°C 70% RH (relative humidity)). This is presumably because water and methanol are applied to the back surface of the paper base layer during printing, stretching the fibers on the back surface of the paper base layer in advance, thereby achieving a balance between the front and back surfaces even if the fibers of the paper base layer on the printing layer side are stretched due to moisture absorption, thereby suppressing convex curl.
[0087] In the case of Comparative Example 1-2, the air permeability was more than 150,000 seconds, and the occurrence of blisters was significant. In contrast, the covering materials of Examples 1-1 and 1-2 both had air permeabilities of 150,000 seconds or less, and it was found that the occurrence of blisters was suppressed.
[0088] Furthermore, from the correlation between the air permeability value and the occurrence of blisters, it was found that blisters can be suppressed when the air permeability is 150,000 seconds or less.
[0089] {Making the lid material 2} Example 2-1 The resin coating agent was a water-based PVDC coating agent at 1.6 g / m 2 A laminate for a lid material of Example 2-1 was produced in the same manner as in Example 1-1, except for coating.
[0090] Example 2-2 The resin coating agent was a water-based PVDC coating agent at 1.1 g / m 2 A laminate for a lid material of Example 2-2 was produced in the same manner as in Example 1-1, except for coating.
[0091] Example 2-3 The resin coating agent was a water-based polyester coating agent at 1.3 g / m 2 A laminate for a lid material of Example 2-3 was produced in the same manner as in Example 1-1, except for coating.
[0092] Example 2-4 As a resin coating agent, a water-based PVOH coating agent was used at 0.7 g / m 2 A laminate for a lid material of Example 2-4 was produced in the same manner as in Example 1-1, except for coating.
[0093] Comparative Example 2-1 Instead of a resin coating agent, a moisturizing agent (polyethylene glycol) is used at 1.5g / m 2 A laminate for a lid material of Comparative Example 2-1 was produced in the same manner as in Example 1-1, except for coating.
[0094] Comparative Example 2-2 The resin coating agent was a styrene acrylic coating agent at 2.3 g / m 2 A laminate for a lid material of Example 2-2 was produced in the same manner as in Example 1-1, except for coating.
[0095] Measurement and Evaluation The laminates for the lid material of each of the examples and comparative examples prepared above were subjected to "evaluation of curl occurrence," "measurement of moisture absorption amount," and "measurement of air permeability" in the same manner as in "Preparation of lid material 1." The obtained results are shown in Table 3.
[0096] [Table 3]
[0097] As is clear from the results in Table 3, the lid materials of each Example (Example 2-1 to Example 2-4) had a moisture absorption of 3.2 g / m at 23° C. and 50% RH (relative humidity) for 60 minutes. 2It was found that the occurrence of curling was improved as compared with Comparative Example 1-1.
[0098] In contrast, the lid materials of Comparative Examples 2-1 and 2-2 both had a moisture absorption of 3.2 g / m at 23°C, 50% RH (relative humidity) for 60 minutes. 2 It was found that the occurrence of curling was aggravated when the thickness was above 100 mm.
[0099] Although no evaluation was conducted on the occurrence of blisters, based on the results of Table 2 above, that "blisters can be suppressed when the air permeability is 150,000 seconds or less," it is presumed that all of the lid materials in the examples and comparative examples in Table 3 can suppress the occurrence of blisters. [Explanation of symbols]
[0100] 10 printing layers 10a Ink layer 10b Overprint varnish layer 20 paper layers 20a Resin coating agent 20b Paper base layer 30 Sealant Layer 40 Barrier Layer 100, 200 Lid material
Claims
1. A lid material having a printing layer, a paper layer, and a sealant layer, The lid material was dried in a vacuum oven at 60° C. for 4 hours, and the mass after drying was used as a reference. When seasoned for 60 minutes at 23°C and 50% RH (relative humidity), the moisture absorption was 3.2 g / m 2 is as follows: The paper layer is coated with a resin coating agent from the printing layer side on the paper base layer, and The laminate of the printed layer and the paper layer has an air permeability of 150,000 seconds or less when measured from the paper base layer side to the printed layer side using an Oken-type testing machine method according to JIS P8117:2019. Lid material.
2. The coating amount of the resin coating agent is 0.5 to 3.0 g / m 2 The lid material according to claim 1 .
3. 3. The lid material according to claim 1 or 2, wherein the resin coating agent comprises a resin selected from the group consisting of polyvinylidene chloride, polyester, polyvinyl alcohol, and combinations of two or more of these.
4. Further comprising a barrier layer; The covering material according to claim 1 or 2, comprising the printing layer, the paper layer, the barrier layer, and the sealant layer in this order.
5. The covering material according to claim 4, wherein the barrier layer is selected from the group consisting of a metal foil layer, an inorganic vapor deposition layer, an organic coating layer, and a combination of two or more of these.
6. The cover material according to claim 1 or 2, wherein the printed layer comprises an ink layer and an overprint varnish layer on the ink layer.
7. The method for producing a covering material according to claim 1 , comprising: applying the resin coating agent to a surface of the paper base layer that is to be laminated with the printed layer to obtain the paper layer.
8. The method of claim 7 , wherein the resin coating comprises a resin selected from the group consisting of polyvinylidene chloride, polyester, polyvinyl alcohol, and combinations of two or more thereof.
Citation Information
Patent Citations
Cover material for paper made cup
JP1997066586A
Heat sealable cover material
JP2000006295A
Lid material
JP2000118546A
Lid material
JP2004196381A